Особливості прийняття управлінських рішень у сфері асортиментної політики - Малюк, С.О. (Культура народов Причерноморья, 2014)
В статье исследованы особенности обоснования и принятия управленческих решений в
сфере ассортиментной политики предприятия. Определены факторы влияния на качество принятия
управленческих решений. Рассмотрена иерархия управления ассортиментом. В частности, исследовано
формирование товарного ассортимента на уровне стратегии, на уровне тактических решений и на
уровне оперативных решений. В ходе исследования определены принципы, которые определяют
последовательность формирования ассортиментной политики предприятия. Разработан алгоритм
принятия решений при наступлении стратегических изменений во внутренней и внешней среде
предприятия. У статті досліджено особливості обґрунтування та прийняття управлінських рішень у
сфері асортиментної політики підприємства. Визначено фактори впливу на якість прийняття
управлінських рішень. Розглянуто ієрархію процесу управління асортиментом. Зокрема, досліджено
формування товарного асортименту на рівні стратегії, на рівні тактичних рішень та на рівні
оперативних рішень. В ході дослідження визначено принципи, що визначають послідовність формування
асортиментної політики підприємства. Розроблено алгоритм ухвалення рішень при настанні
стратегічних змін у зовнішньому та внутрішньому середовищі підприємства. In a rapidly changing market environment, the role played by managing decisions in assortment
policy cannot be overstated. Effectiveness of successful management decisions in the financial and economic
crisis is of particular relevance as rational, reasonable, timely and informed decisions are able to be the start
point to exit from the difficulty of the enterprise. But at the same time, unjustified and wrong decisions can lead
to the worst situations – stagnation, depression, bankruptcy and so on. In such circumstances, the risk increases,
and thus the responsibility of marketing companies that can form by its decisions the optimal competitive range,
or relieve the company prospects to overcome the crisis. This srticle investigates the features of decision-making
in the field of assortment policy of the company. It is determined the factors of influence the quality of decisionmaking.
Considered hierarchy process of making management decisions. In particular, the formation of the
product range is investigated at the level of strategy, tactical and operational decisions. The study defined the
principles governing the formation of a sequence of product policy of the company. It is developed the algorithm
of decision-making in the time of policy changes in the external and internal environment of the company.